2016
DOI: 10.1111/1467-8489.12195
|View full text |Cite
|
Sign up to set email alerts
|

How drought affects the financial characteristics of Australian farm businesses

Abstract: The financial performance of 240 farms in a drought-affected agricultural region of Australia is analysed. The decadal study period included some years of widespread drought, as well as years with only subregional droughts or no drought. Some droughts created larger adverse financial impacts than others. Mostly, the more droughts farms experienced, the worse was their financial performance relative to farms within the same quantile of farm performance. Despite the incidence of drought, by the end of the decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In other words, credit managers are preferably interested in farmers with no drought experience, therefore, drought experience of farmers represents a key determining factor for credit access. The results related to the effect of drought found in this study is supported by the report of Kingwell and Xayavong (2017) who found that the financial performance of farmers heavily depends on the extent of drought experience of farmers.…”
Section: Full Information Maximum Likelihood (Fiml) Estimates Of the Endogenous Switching Probit Model (Espm)supporting
confidence: 87%
“…In other words, credit managers are preferably interested in farmers with no drought experience, therefore, drought experience of farmers represents a key determining factor for credit access. The results related to the effect of drought found in this study is supported by the report of Kingwell and Xayavong (2017) who found that the financial performance of farmers heavily depends on the extent of drought experience of farmers.…”
Section: Full Information Maximum Likelihood (Fiml) Estimates Of the Endogenous Switching Probit Model (Espm)supporting
confidence: 87%
“…A limitation to the modelling approach based on Equations (3) and (4) is that interyear cumulative financial consequences, and their impacts on the viability of farm expansion are not explicitly considered, yet these impacts can be important (Kingwell and Xayavong 2016). Under future, more likely adverse climate change, interyear effects overlooked in this study could more deleteriously affect farm asset values.…”
Section: Summary Of Farm Financial Modellingmentioning
confidence: 99%
“…A number of studies have been carried out to measure the impact of droughts on agricultural activities using input–output tables (Wilhite ; Wittwer and Griffith ; Howitt et al ), farms’ business performance using data from agricultural consulting firms (Lawes and Kingwell ; Kingwell and Xayavong ), farmers’ consumption and income using household surveys (Garbero and Muttarak ) and farms’ resilience to droughts using district‐level production data (Birthal et al ).…”
Section: Literature Reviewmentioning
confidence: 99%